2019
DOI: 10.3390/su11174720
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the Winter Thermal Environment of Bedrooms in Zhongxiang: A Case Study in Rural Areas in Hot Summer and Cold Winter Region of China

Abstract: In this paper, onsite measurements and a subjective questionnaire were conducted to study the thermal environment and heating condition of bedrooms during the winter in rural areas in China’s hot summer and cold winter (HSCW) region. Indoor and outdoor thermal environmental parameters were measured to evaluate the thermal conditions of bedrooms. Thermal sensation/tendency/acceptance, heating, and health condition were investigated to complete the analysis of attitudes of local residents on the thermal environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Simultaneously, many scholars have found that, in winter, low indoor temperature is still prevalent in rural houses of colder northern China [10][11][12]. In recent years, with the development of society and economy, the rural residents' requirements for living comfort have been constantly improved [12][13][14]. If there is no control, the energy consumption in rural residential buildings will continue to increase in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, many scholars have found that, in winter, low indoor temperature is still prevalent in rural houses of colder northern China [10][11][12]. In recent years, with the development of society and economy, the rural residents' requirements for living comfort have been constantly improved [12][13][14]. If there is no control, the energy consumption in rural residential buildings will continue to increase in the future.…”
Section: Introductionmentioning
confidence: 99%
“…The average indoor temperature of rural residential houses in the HSCW zone can reach 29.7 • C in the summer, which indicates that the indoor thermal environment falls beyond the 80% acceptability range of the adaptive model defined by ASHRAE standard 55 [5]. A neutral temperature of 10.7 • C and 80% acceptable lower temperature of 4.7 • C were obtained for bedrooms in rural areas of China's HSCW zone, which further demonstrates the poor indoor thermal environment [6]. In Shanghai, Changsha, and Chongqing, houses were observed to have a high relative humidity of 60%-100% [7].…”
Section: Introductionmentioning
confidence: 93%
“…From the perspective of preference factors, this study takes the house furnishings, lighting for decoration and various materials and textures in a single bedroom space into investigation. On the one hand, it enriches the composition of the physical environment elements of the elders' residence [11][12][13], on the other hand, it supplements the hardware requirements which need paying attention to the interior design of the bedroom environment of an elderly-friendly residence.…”
Section: ) Correlations Between Physical Condition and Bedroom Living...mentioning
confidence: 99%
“…On the one hand, focusing on the overall quality assessment of the indoor environment [10,11], scholars provide theoretical support for the design of senior housing by studying the impact of the overall physical environment on the elderly population in senior living institutions or senior housing [10]. On the other hand, they focus on a single element of the physical environment, such as sound, heat, light, and air quality, evaluating a single element of the physical environment in senior housing and then making recommendations for optimization [12][13][14]. Meanwhile, some scholars have researched the relationship between two physical environments.…”
Section: Introductionmentioning
confidence: 99%